RESEARCH ON DIGITAL MEDIA MARKETING TRENDS BASED ON PRINT MEDIA - Arsyadona; Angga Syahputra (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2025)
This study aims to examine the research trends of print media-based digital marketing media, as well as explore how these two media can complement each other in effective marketing strategies. In the context of digitalization, print media has faced major challenges but remains relevant in several market segments. This study aims to identify the role that print media still plays in the digital era, as well as analyze how the integration between digital marketing and print media can improve business reach and performance, especially for small and medium enterprises (SMEs). The method used in this study is a qualitative method with a case study approach, where data is collected through in-depth interviews with SMEs in the tourism sector and analysis of the content of their marketing campaigns. The data used came from interviews with SMEs using a combination of digital and print media, as well as from literature that researched marketing trends in both media. The results of the study show that even though digital marketing dominates, print media still has high credibility in the eyes of certain consumers. SMEs that combine these two mediums show significant performance improvements, especially in terms of consumer loyalty and local market outreach. The study also found that the main challenge faced by SMEs in utilizing digital media is the lack of adequate knowledge and resources. The implications of these findings underscore the importance of training and support for SMEs to optimize integrated marketing strategies that effectively leverage digital and print media.